Improving the efficacy of anti-SSEA4 antibody in pancreatic cancer immunotherapy with glyco-optimization and immune checkpoint blockade - Po-Kai Chuang; Cinya Chung; Kuo-Shiang Liao; Chi-Huey Wong (Proceedings of the National Academy of Sciences, 2025)
Pancreatic cancer remains one of the most lethal malignancies with limited therapeutic options. Among the alternative targets explored for pancreatic cancer, the glycolipid stage-specific embryonic antigen-4 (SSEA4) has been extensively studied. We have previously demonstrated that the chimeric anti-SSEA4 antibody with alpha-2,6-sialylated complex type biantennary glycan (SCT) or its 3-fluorosialyl derivative (FSCT) attached to the Fc-Asn297 residue exhibited enhanced binding to the Fc-receptors FcγRIIIA and FcγRIIA which are responsible for antibody-dependent cellular cytotoxicity and phagocytosis as well as vaccinal effect. Here, we found that high-SSEA4 expression correlates with increasing tumor proliferation and sensitivity to the glyco-optimized antibodies (anti-SSEA4-SCT and anti-SSEA4-FSCT) which preferentially recruit NKG2D-expressing natural killer cells and FcγRIIA-bearing macrophages with enhanced target killing activity. We also uncovered an immune evasion mechanism involving the interaction of sialoglycans on the cancer cell with Siglec-9 on NK cells or Siglec-10 on macrophages to block the antibody-mediated effector functions, and this immune checkpoint inhibition can be suppressed with the removal of sialic acid on cancer cells or blockade of Siglec recognition. In xenograft models, the glyco-optimized antibodies exhibited superior inhibition of tumor growth with high-SSEA4 expression compared to the wild-type antibody and persistent antitumor activity without additional antibody administration. These findings support anti-SSEA4 antibodies with enhanced effector functions and blockade of Siglec-mediated immune checkpoint as a promising therapeutic strategy for pancreatic cancer.